MANGKUNEGARAN SURYASUMIRAT (HKMN) RELATIVES ASSOCIATION'S POLITICAL PROCESS IN INTERNALIZING LOCAL VALUES AND UTILIZING THE NATIONAL STRATEGIC RESOURCES DURING THE NEW ORDER REGIME (1966-1998) - Diana Fawzia (JILPR Journal Indonesia Law and Policy Review, 2023)
HKMN Suryasumirat is a kinship-based organization for Javanese royal elites from Surakarta that held an important role during the New Order era. The organization that was established in 1946 managed to transform itself in order to adapt to the complex urban environment and became one of the most influential interest groups. The New Order regime's patrimonial characteristic provided opportunities to thrive with the support of the reigning regime. Through various political processes HKMN Suryasumirat managed to dominantly utilize the country's national strategic resources, in economy, politics, and military, even had the Mangkunegaran values adopted as national moral values. This research focuses on the relations between the presence of HKMN Suryasumirat, its limitations of resources, social-political background, and its efforts to increase its role in order to control existing resources through a series of political processes. They also managed to control several strategic resources during the New Order. The time context employed in this research (New Order regime from 1966-1998) is not used intensively as one of the determining factors of the condition, but it should be seen as the context of the review.